Inhibition of sulfate-reducing bacteria influenced corrosion on hydrophobic poly(dimethylsiloxane) coatings. (1st September 2020) - Arukalam, Innocent O.; Njoku, C.N.; Yang, Lihui; Hou, Baorong; Li, Ying
Abstract: Sulfate-reducing bacteria (SRB) has been pointed out as one of the causative agents of microbial induced corrosion in the marine environment. To address this problem, novel strategies are being experimented as against the earlier methods which have been banned due to their toxic effects on useful aquatic lives. Thus, the aim of this study was to investigate the effect of non-toxic perfluorodecyltrichlorosilane (PFDTS) on resistance of hydrophobic poly(dimethylsiloxane)/phosphoric acid-treated zinc oxide (PDMS/PA-treated ZnO) coatings to SRB-induced biofouling and corrosion. The surface features of the coatings before and after exposure to SRB/NaCl solution were analyzed by scanning electron microscopy (SEM). Wettability of the coatings before and after exposure was also measured. The interaction of SRB with the coatings was investigated by FTIR spectroscopy. The resistance performance of the modified coatings against SRB-induced corrosion was monitored by electrochemical impedance spectroscopy (EIS). The EIS measurements revealed that 0.20 g PFDTS-based coating displayed highest corrosion resistance with impedance modulus of 6.301 × 10 10 after 15 d of exposure to SRB/NaCl medium. The results were corroborated by surface and chemical interaction analyses, and thus, indicate that 0.20 g PFDTS-modified PDMS/PA-treated ZnO coating has potentials for excellent SRB-induced corrosion resistance and anti-biofouling performance.